Peran Kegiatan Ekstrakurikuler BTQ dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa di SMPN 8 Percut Sei Tuan - Neliwati; Siregar, Fahriza Hasri; Wildan Sitorus; Pane, Nova Emiliya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Qur’an as a guide to life for Muslims should be studied by constantly reading, interpreting, memorizing and interpreting it. Nowadays, there are many junior high school students who cannot read the Koran according to the correct tajwid, and even make mistakes in pronunciation of the makhorijul letters, and do not know the hijaiyah letters. So there is a need for BTQ extracurricular roles. The aim of this research is to determine the role of BTQ extracurricular activities in improving students' Al-Qur'an reading skills at SMPN 8 Percut Sei Tuan. This research uses qualitative methods using a descriptive approach. The subjects in this study are the Principal, the Person in Charge of BTQ extracurricular, BTQ Extracurricular Trainer, and students. The results showed that BTQ's extracurricular program has an important role in improving the reading skills of students at SMPN 8 Percut Sei Tuan. Although not optimal, when reading the Qur'an students at SMPN 8 Percut Sei Tuan are able to pronounce hijaiyah letters in accordance with the makhorijul letters, are able to recognize the letters that are part of the science of tajweed, understand the theory and can remember examples of tajweed, such as nun sukun, mim sukun and tanwin, so that it can be said to be able to apply the science of tajweed in reading the Qur'an and fluent in reading it.